2007
DOI: 10.1002/ajmg.a.31729
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent interstitial deletions of proximal 18q: A new syndrome involving expressive speech delay

Abstract: Most deletions of the long arm of chromosome 18 involve some part of the most distal 30 Mb. We have identified five individuals with cytogenetically diagnosed interstitial deletions that are all proximal to this commonly deleted region. The extent of their deletions was characterized using molecular and molecular cytogenetic techniques. Each participant was assessed under the comprehensive clinical evaluation protocol of the Chromosome 18 Clinical Research Center. Three of the five individuals were found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 20 publications
3
38
0
2
Order By: Relevance
“…Mental retardation is found in case reports of all three abnormalities (18p-, 18q-, and 18p tetrasomy), and in one study was estimated at 68% of all 18q deletion subjects [Semrud-Clikeman et al, 2005]. Abnormal EEG findings and epilepsy have been described in case reports for all three chromosomal disorders [Chudley et al, 1974;Wilson et al, 1979;Wilson and Al Saadi, 1989;Schinzel et al, 1991;Chudley et al, 1992;Krasikov et al, 1992;Poissonnier et al, 1992;Engelen et al, 1998;Tinkle et al, 2003;Linnankivi et al, 2006;Swingle et al, 2006;Brenk et al, 2007;Cody et al, 2007]. Many subjects with 18p or 18q deletions display delayed speech, mutism, or articulation difficulties [Thompson et al, 1986;Poissonnier et al, 1992;Grosso et al, 1999;Babovic-Vuksanovic et al, 2004;Wester et al, 2006;Brenk et al, 2007;Cody et al, 2007] and there has been one report of short Neuropsychiatric Genetics attention span in three out of three 18p-subjects [Thompson et al, 1986].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Mental retardation is found in case reports of all three abnormalities (18p-, 18q-, and 18p tetrasomy), and in one study was estimated at 68% of all 18q deletion subjects [Semrud-Clikeman et al, 2005]. Abnormal EEG findings and epilepsy have been described in case reports for all three chromosomal disorders [Chudley et al, 1974;Wilson et al, 1979;Wilson and Al Saadi, 1989;Schinzel et al, 1991;Chudley et al, 1992;Krasikov et al, 1992;Poissonnier et al, 1992;Engelen et al, 1998;Tinkle et al, 2003;Linnankivi et al, 2006;Swingle et al, 2006;Brenk et al, 2007;Cody et al, 2007]. Many subjects with 18p or 18q deletions display delayed speech, mutism, or articulation difficulties [Thompson et al, 1986;Poissonnier et al, 1992;Grosso et al, 1999;Babovic-Vuksanovic et al, 2004;Wester et al, 2006;Brenk et al, 2007;Cody et al, 2007] and there has been one report of short Neuropsychiatric Genetics attention span in three out of three 18p-subjects [Thompson et al, 1986].…”
mentioning
confidence: 92%
“…In studies of persons with chromosome 18p-deletions, there have been reports of two persons with autism [Ghaziuddin et al, 1993;Wester et al, 2006], and one person with paranoid psychosis, depression, and subclinical obsessive compulsive disorder [Babovic-Vuksanovic et al, 2004]. In studies of 18q-syndromes, there have been individual reports of autistic features in 8 subjects [Wilson and Al Saadi, 1989;Schinzel et al, 1991;Poissonnier et al, 1992;Mahr et al, 1996;Tinkle, 2003;Linnankivi et al, 2006], attention deficit and/or hyperactivity disorder in 6 subjects [Surh et al, 1991;Chudley et al, 1992;Mahr et al, 1996;McEntagart et al, 2001;Tinkle, 2003;Cody et al, 2007], and violent/aggressive behaviors have been reported in 14 subjects [Chudley et al, 1974;Wilson and Al Saadi, 1989;Poissonnier et al, 1992;Mahr et al, 1996;McEntagart et al, 2001;Tinkle, 2003]. There is only one report of a behavioral/psychiatric problem in a case of chromosome 18p tetrasomy; an individual who had a history of aggressive, selfinjurious, and destructive behavior [Swingle et al, 2006].…”
mentioning
confidence: 96%
“…An intense literature [Cody et al, 2007;Smith, 2007;Gibson and Gruen, 2008;Fisher and Scharff, 2009;Caglayan, 2010;Newbury and Monaco, 2010;Scherer and Dawson, 2011] and database (http://www.mindspec.org/autdb.html) research revealed 244 genes associated with human-specific communication ( table 1 ). These genes have been associated with autism spectrum, reading, speech, and language disorders.…”
Section: Database Analysesmentioning
confidence: 99%
“…Interestingly, individual 18q-104C had a proximal interstitial deletion of 18q and is the only one of Wve with essentially the same deletion who had an AQ score indicating a high probably of autism (Cody et al 2007). However, one genetic diVerence between this individual and the other four interstitial deletions is the presence of a second small (3.5 Kb) 18q interstitial deletion between the NETO1 and the FBXO15 genes.…”
Section: Discussionmentioning
confidence: 99%